Listening to factually incorrect sentences activates classical language areas and thalamus - Yu, Tao; Lang, Simone; Birbaumer, Niels; Kotchoubey, Boris (Neuroreport, 2011)
Neurophysiological underpinnings of the integration of information during sentence comprehension have been studied since 1980. However, little is known about integrative processes in sentences containing a word that is semantically congruent, but factually incompatible with the context. In this study, we aimed at investigating the differences between the brain regions involved in responses to factually correct and incorrect sentences. Eighteen healthy volunteers underwent functional MRI while listening passively to 40 correct and 40 incorrect sentences. The contrast between factually correct and incorrect sentence endings revealed large activation areas in the left inferior frontal gyrus, the left middle/superior temporal gyrus, and smaller activations of these areas’ homologs in the right hemisphere, in the thalamus, and Brodmann area 6.